The black circle [compact disc, unabridged] - Carman, Patrick (39 clues, 2009)
In the first 39 Clues book, Amy and Dan Cahill discovered that they're part of one of the most powerful families in human history. Passing up the hush money, the siblings set out to uncover the 39 clues which would reveal the source of their family's awesome power. In each subsequent book, the siblings attempt to discover one clue at a time. Here, in the fifth book, Amy and Dan find themselves on their most dangerous adventure yet as they investigate Lucian secrets and elude Irina Spasky.